Effect of phosphorus on yield and economics of maize (Zea mays) under semi-arid conditions of Afghanistan - Ahmadi, N M; Das, T K; Nasrat, N; Rathore, S S; Paul, A K (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted at the Afghanistan National Agricultural Science and Technology University (ANASTU), Kandahar, Afghanistan during 2015 to find out the optimum level of P in maize. Seven phosphorus levels at 0 (control), 15, 30, 45, 60, 75 and 90 kg P2O5/ha were laid out in a randomized complete block design with three replications. Results showed that the application of 75 kg P2O5/ha resulted in maximum number of cobs/plant (1.8), number of cob/m (12.4), cob girth (14 cm), cob diameter (4.4 cm), thousand grain weight (261.2 g), grain yield (6.51 t/ha) and biological yield (19.43 t/ha) compared to those in control. A dose of 73.6 kg P2O5/ha based on grain yield, and a dose of 86.7 kg P2O5/ha based on biological yield of maize were economic optimum doses of P in maize. But, the 75 kg P2O5/ha resulted in highest values of most of the yield attributes, leading to highest grain, stover and biological yields and net returns. Therefore, a 75 kg P2O5/ha may be advocated to maize along with the recommended 150 kg N/ha, 20 kg K2O/ha and 25 kg ZnSO4/ha for obtaining higher yield and income in Kandahar, Afghanistan.